Influenza vaccine effectiveness during the 2012 influenza season in Victoria, Australia: Influences of waning immunity and vaccine match. Issue 6 (8th November 2013) - Sullivan, Sheena G.; Komadina, Naomi; Grant, Kristina; Jelley, Lauren; Papadakis, Georgina; Kelly, Heath
Abstract Vaccine effectiveness may wane with increasing time since vaccination. This analysis used the Victorian sentinel general practitioner (GP) network to estimate vaccine effectiveness for trivalent inactivated vaccines in the 2012 season. A test‐negative design was used where patients presenting to GPs with influenza‐like illness who tested positive for influenza were cases and noncases were those who tested negative. Vaccination status was recorded by GPs. Vaccine effectiveness was calculated as (1‐odds ratio) × 100%. Estimates were compared early versus late in the season and by time since vaccination. Virus isolates were assessed antigenically by hemagglutination inhibition assay in a selection of positive samples and viruses from healthy adults who experienced a vaccine breakthrough were analyzed genetically. The adjusted vaccine effectiveness estimate for any type of influenza was 45% (95% CI: 8, 66) and for influenza A(H3) was 35% (95% CI: −11, 62). A non‐significant effect of waning effectiveness by time since vaccination was observed for A(H3). For those vaccinated <93 days of presentation vaccine effectiveness was 37% (95% CI: −29, 69), while for those vaccinated ≥93 days before presentation it was 18% (95% CI: −83, 63). Comparison of early versus late in the season estimates was very sensitive to the cut off week chosen for analysis. Antigenic data suggested that low vaccine effectiveness was not associated with poor vaccine match among the A(H3) viruses. However, genetic analysis suggested nucleotide substitutions in antigenic sites. In 2012, the trivalent influenza vaccine provided moderate protection against influenza and showed limited evidence for waning effectiveness. Antigenic and genetic data can provide additional insight into understanding these estimates. J. Med. Virol. 86:1017–1025, 2014. © 2013 Wiley Periodicals, Inc.